Membangun Kohesi Sosial Melalui Unplugged Pedagogy: Sebuah Ulasan Perspektif Mengenai Pendekatan Psikologi Sosial Dalam Kelas Inklusi - Rosmawaty Rumahorbo; Dedi Kuswandi; Ika Andrini Farida (Institut Agama Kristen Negeri (IAKN) Ambon, 2025)
Abstract: Social cohesion is a critical foundation for the realization of meaningful inclusive education; however, challenges such as prejudice, isolation, and unequal group dynamics often hinder its development in the classroom. This conceptual article argues that unplugged pedagogy can serve as an effective and contextual medium to operationalize the core principles of social psychology in building social cohesion. By synthesizing key theories such as the Contact Hypothesis, Social Interdependence Theory, and Social Identity Theory, the article outlines three integration mechanisms: (1) facilitating positive and equal intergroup contact through structured simulations and role-playing; (2) fostering a common ingroup identity through collaborative projects and cooperative problem-solving; and (3) reducing stereotype threat through reflective dialogue and the creation of inclusive classroom norms. A conceptual framework is proposed to map the systematic relationship between psychosocial principles, unplugged activity design, and expected outcomes in classroom climate. This framework serves as a hypothesis that requires further empirical testing. As an integration, the conceptual framework offers a theoretically grounded, practical, and sustainable approach to transforming social dynamics in inclusive classrooms. Its practical implications are directed toward educators in designing learning activities, as well as policymakers and curriculum developers in advancing inclusive education that is not only adaptive but also socially transformative. Keywords: social cohesion, unplugged pedagogy, social psychology, inclusive education, experiential learning